2015
DOI: 10.1039/c5ra13891d
|View full text |Cite
|
Sign up to set email alerts
|

ZrO2-β-cyclodextrin catalyzed synthesis of 2,4,5-trisubstituted imidazoles and 1,2-disubstituted benzimidazoles under solvent free conditions and evaluation of their antibacterial study

Abstract: A series of 2,4,5-trisubstituted imidazoles and 1,2-disubstituted benzimidazoles catalyzed by ZrO2-supported-β-cyclodextrin (ZrO2-β-CD) under solvent free conditions have been synthesized and characterized by spectral methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“… Entry Catalyst Solvent/Temperature Time (min) Yield (%) Ref. 1 Cellulose/Fe 2 O 3 /Ag (0.015 g) Solvent-Free/100 °C 10 91 [ 45 ] 2 l -Proline (15 % mol) MeOH/Reflux 540 90 [ 46 ] 3 Silica sulfuric acid (0.5 g) H 2 O/Reflux 240 73 [ 47 ] 4 TiCl 4 .SiO 2 (50 mol%) Solvent-Free/110 °C 300 92 [ 48 ] 5 Fe 3 O 4 @PVA-SO 3 H (0.5 g) EtOH/r.t 40 98 [ 41 ] 6 ZrO 2 -β-CD (40 % mol) Solvent-Free/100 °C 24 96 [ 49 ] 7 ZnS–ZnFe 2 O 4 (0.02 g) Ultrasonic/70 °C 15 95 [ 44 ] 8 MgAl CO 3 -LDH@Asn EtOH/Reflux 20 ...…”
Section: Resultsmentioning
confidence: 99%
“… Entry Catalyst Solvent/Temperature Time (min) Yield (%) Ref. 1 Cellulose/Fe 2 O 3 /Ag (0.015 g) Solvent-Free/100 °C 10 91 [ 45 ] 2 l -Proline (15 % mol) MeOH/Reflux 540 90 [ 46 ] 3 Silica sulfuric acid (0.5 g) H 2 O/Reflux 240 73 [ 47 ] 4 TiCl 4 .SiO 2 (50 mol%) Solvent-Free/110 °C 300 92 [ 48 ] 5 Fe 3 O 4 @PVA-SO 3 H (0.5 g) EtOH/r.t 40 98 [ 41 ] 6 ZrO 2 -β-CD (40 % mol) Solvent-Free/100 °C 24 96 [ 49 ] 7 ZnS–ZnFe 2 O 4 (0.02 g) Ultrasonic/70 °C 15 95 [ 44 ] 8 MgAl CO 3 -LDH@Asn EtOH/Reflux 20 ...…”
Section: Resultsmentioning
confidence: 99%
“…The 80–96% of the products were obtained in 1–1.4 h at 100°C (Scheme ). The catalyst reusability was for four runs . Ahmadian et al ., using the same protocol, proposed a green solvent‐free synthesis of 2‐aryl‐1‐arylmethyl‐1 H ‐1,3‐benzimidazoles ( 27 ) by employing cobalt manganese oxide nanoparticles as catalyst.…”
Section: Nano‐transition Metal Catalyzed Oxidative Coupling Of O‐phenmentioning
confidence: 99%
“…Girish et al [ 39 ] reported the synthesis of 2-phenyl imidazole derivatives by the addition reaction using nano ZrO 2 -β-cyclodextrin as a supramolecular catalyst in good yield ( Scheme 14 a). In addition, the catalyst can be recycled to facilitate resource conservation.…”
Section: Application Of Cyclodextrin In Conventional Reactionmentioning
confidence: 99%